Modernization and society-nature relationship. Capitalism in the passage to the 21st century - Alfredo, Anselmo (GEOUSP Espaço e Tempo (Online), 2023)
The contradiction use value  exchange value, identity of merchandise, expresses the  metaphisic (social work time, or even value) trough the natural (physical form of the merchandise). The given universality of merchandise, this quirk between natural and social, fetish, in the mature Marx´s critique, constitutes itself as the universal conscience belonged to the subject socialized by capital. From capital point of view, the physical expansion of capital investiments determined by the reduction of its metaphysic, is phenomenalized itself trough its opposite form, as if it were pure positive growth of its accumulation. The 1970’s are considered as a turn of century, from productive capital to ficticious one. Here the naturalization, strictly by the value form, cannot replenish value, wich becomes necessary the constitution of a speech refering to nature, expressed in the enviromentalism, a generic conscienscioness. Rome Club here, is put himself as fundamental expression of the ficticious capital physiocraci. Even more, the fetishism of capital is also considered through the median cities teory and its analysis of real state business.